(untitled) (Italian Journal of Public Health, 2009)
Human papillomaviruses (HPVs) comprise more than 180 genotypes. HPV infection is mainly diagnosed by molecular methods. The aim of our study was to review the main molecular methods used to diagnose HPV infection, underscoring their characteristics. Several methods have been developed for molecular diagnosis of Papilloma infection, such as those based on PCR technique. Another commercial non-PCR based diagnostic method is Hybrid Capture test; it is the only commercially available HPV DNA detection test approved by the FDA. Several Authors have suggested that viral load and E6/E7 transcripts could be used as surrogate markers of persistent HPV infection, being more specific predictors of progressive disease than the simple presence of HPV DNA. Validating clinical sensitivity and specificity of each technique and improving the interpretation of the results are essential; consequently, there is a clear need for well characterized international quality control panels to compare the various diagnostic methods. HPV DNA testing could be useful both as a primary screening test, alone or in combination with a Pap smear, for the early detection of cervical cancer precursors, and as triage test to select women with minor cytological abnormalities who will need further follow-up and to predict possible treatment failure in women with diagnosed high-grade intraepithelial lesions who have undergone excisional therapy. In the next future surveillance for HPV infections, based on these molecular methods, could represent an important step for the development of primary and secondary prophylactic interventions, such as new vaccines targeted to genotypes who might replace those previously prevalent.